The impact of academic dropout at the University of Granada and proposals for prevention12 - González-González, Daniel; Arias-Corona, María; Cárdenas-Cruz, Antonio; Vicente-Bújez, Alejandro (Frontiers in Education, 2023)
Persistence and dropout are two sides of the same coin. Together with personal and social factors, issues associated with the quality of teaching provided by universities determine students’ decision to persist in pursuing their academic degree or, on the contrary, to drop out of university studies. Our working hypothesis is that the impact on improving the quality of teaching by considering pedagogical factors which are currently being researched and experimented with, can improve the overall persistence rate by reducing the dropout rate. In this preliminary study we intend to make a first approach to the phenomenon of academic failure in Andalusian universities from the prediction and diagnosis of risk groups and the recommendation of preventive measures. Among the measures we propose for prevention, we highlight those that have an impact on pedagogical factors. Our work consisted of applying an instrument designed to diagnose the risk of dropping out of university studies to a sample of first-year university students at the University of Granada. The instrument was applied at the beginning of the second semester. Of the 642 pupils surveyed, we established a risk group of 20 students. We propose measures targeting the factors that predict dropout and the implementation of preventive measures.